Legal Case Summaries as Content-Based Instruction Material to Improve Law Students’ Reading Comprehension - Orun, Putri Anugraheli Ramba; Jannah, Miftahul (Indonesian Research Journal on Education, 2026)
The primary objective of this study is to examine the effectiveness of legal case summaries as content-based instruction (CBI) materials in enhancing the reading comprehension skills of law students in the context of English for Specific Purposes (ESP). Conducted using a quasi-experimental one-group pretest-posttest design, the research involved 30 second-semester law students at Sekolah Tinggi Ilmu Hukum Biak-Papua. Over a four-week period, students were taught using simplified legal case summaries integrated into English reading instruction. A total of 20 multiple-choice items were used to assess reading comprehension before and after the intervention. The findings revealed a significant improvement in students’ average scores, from 47.33 in the pre-test to 60.33 in the post-test. A paired sample t-test produced a t-value of 6.94 and a p-value < 0.001, confirming the statistical significance of the improvement. These results support the integration of field-specific content in language teaching, in line with CBI and ESP principles, while also demonstrating how simplified legal materials help manage cognitive load, as explained by Cognitive Load Theory (CLT). Practically, this instructional approach provides ESP lecturers with a relevant and effective model for teaching Legal English in higher education settings.